The Relationship Between Biopsychosocial Characteristics and Perceived Social Support and Anxiety Among Female Students - Reni Merta Kusuma (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Background: Anxiety is one of the most common mental health problems in female students, influenced by various biopsychosocial factors. Social support is known to reduce anxiety, yet the specific role played by different sources of support remains rarely examined in highly homogeneous groups of young women. Objective: This study aimed to identify the relationship between biopsychosocial characteristics, perceived social support from various sources, and anxiety levels in single, parent-dependent female midwifery students. Method: This cross-sectional study involved 43 female midwifery students at a private university in Indonesia. Data were collected using a biopsychosocial questionnaire, Multidimensional Scale of Perceived Social Support (MSPSS), and Hamilton Anxiety Rating Scale (HAMA). Data analysis used descriptive, Cramer’s V, Mann-Whitney, and Spearman’s rank correlation. Results: The presence of physical illness was significantly associated with higher anxiety levels (p = 0.03). Perceived support from significant others showed a significant negative correlation with anxiety (r = -0.38; p = 0.01), while support from family and friends did not reach statistical significance. After dichotomization, the low-support group from significant others (n=2) had a median HAMA score of 20 compared to 10 in the high-support group (n=41), although the difference was not statistically significant (Mann-Whitney U = 2.000; p = 0.462) due to the very small low-support group. Boxplot visualization showed a clinically meaningful increase in median HAMA scores in the low-support group across all MSPSS domains. Conclusion: In young, single, parent-dependent female students, physical illness and low perceived support from significant others (partner/mentor) are the strongest predictors of anxiety.